Factors affecting customer loyalty towards AirAsia Airline in Kota Kinabalu / Muhammad Nazrin Mansor - Mansor, Muhammad Nazrin (2016)
AirAsia was established in 1993 and began operations on 18 November 1996. It was founded by a government-owned conglomerate, DRB-Hicom. AirAsia Berhad is a Malaysian low-cost airline headquartered near Kuala Lumpur, Malaysia. It is the largest airline in Malaysia by fleet size and destinations, and Asia's largest low-cost airline by passengers carried and jet fleet. Thus, this research is to identify the factors affecting customer loyalty towards AirAsia airline in Kota Kinabalu. The respondents are selected randomly from the Kota Kinabalu AirAsia airline passenger. The total of 200 questionnaires was distributed to the potential respondents.